NAEFIA WETZEL 1930 FROM THE QUIRIQUINA FORMATION (LATE MAASTRICHTIAN, CHILE) : RELATIONSHIP TO MODERN SPIRULA AND ANCIENT COLEOIDEA (CEPHALOPODA) - Bandel K.; Stinnesbeck W. (My University, 2006)
The shell of Naefia neogaeia Wetzel, 1930 from the Maastrichtian of Chile is revised and compared with other Cretaceous taxa placed in the Groenlandibelidae. Naefia differs from these species by the absence of a rostrum and other external layers of the shell, and a rectangular tissue attachment scar. The thorn-like dorsal proostracum is another distinctive feature of Naefia. Shell characters found in Spirula and Sepia do not favor a relation with Naefia, which would then not fit any group proposed, in literature. Naefia, as well as Groenlandibelus, remain isolated regarding their taxonomic position among fossil coleoids.
Keywords: COLEOIDEA; CRETACEOUS; EVOLUTION; MOLLUSCA; SHELL CONSTRUCTION; Mesozoic::Cretaceous